Molecular Genetic Analysis of Factor XI Deficiency: Identification of Five Novel Gene Alterations and the Origin of Type II Mutation in Portuguese Families - Ventura, Célia; Santos, Ana I. M.; Tavares, Alice; Gago, Teresa; Lavinha, João; McVey, John H.; David, Dezsö (Thrombosis and Haemostasis, 2000)
Coagulation factor XI (FXI) deficiency is an inherited autosomal recessive mild bleeding disorder. In this study, we report the molecular genetic analysis of FXI deficiency in six unrelated families of Portuguese origin. The Jewish type II mutation was found in two families, of seemingly Portuguese origin. Haplotype analysis in these families demonstrated that this mutation is of Jewish origin. In the remaining families, five novel FXI mutations have been identified. Two of these mutations (FXI IVS K -10T→A and FXI 1026G→T, cd 324) affect the FXI pre-mRNA splicing. A further two (FXI 307 ins AAGCAAT, cd 85 and FXI 1072 del A, cd 340) introduce frameshifts leading to premature termination codons. The FXI splicing mutation, 1026G→T cd 324, was found in compound heterozygosity with missense mutation FXI K518N. Analysis of the FXI mRNA from the latter genotype demonstrated new donor splice site usage. All reported mutations most likely result in functional null-alleles. In addition, three novel polymorphisms have been identified: at nt -138 in intron A, at codon D125 in exon 5 and at codon T249 in exon 8.
Keywords: FXI deficiency; phenotype; FXI mutations; FXI pre-mRNA splicing; origin of the type II mutation